A Decoupling Method with Different Subdomain Time Steps for the Non-Stationary Navier-Stokes ⁄ Darcy Model (Journal of Computational Mathematics, 2018)
A decoupling method with different subdomain time steps for the non-stationary Navier-Stokes/Darcy model is formulated and analyzed. The method has asynchronous time steps, which adopt small time steps in the fluid region and large time steps in the porous region. It saves relatively large amount of CPU time. Stability and convergence of the method are proved. The numerical results are presented to illustrate the features of the proposed method.